The Development of Android-Based Digital Pocketbook Learning Media on Short Story Materials - Idham Syafri Marliansya; Ratu Wardarita; Muhammad Ali; Gunawan Ismail (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
The aims of this study were: a) to describe the needs of students and teachers for android-based digital pocketbook learning media at SMK Negeri 1 Palembang; b) to describe the results of the design of android-based digital pocketbook learning media at SMK Negeri 1 Palembang; and c) to describe the validation results of android-based digital pocketbook learning media at SMK Negeri 1 Palembang. In the method used in this development, researchers refer to the research and development (R&D) model using the "ADDIE Model," which has five stages, namely: 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. The results in this study were trials conducted on validators, namely: 1) material experts obtained a score of 41 on average 4.6 in the Very Good category by revising suggestions and comments provided by the validator; 2) linguists got an average score of 23 4.6 in the Very Good category by revising suggestions and comments provided by the validator; and 3) media experts got an average score of 35 4.37 in the Very Good category by revising the suggestions and comments provided by the validator.